Digital panoramic radiography for diagnosis of the temporomandibular joint: CBCT as the gold standard - Daniela Brait Silva LADEIRA; Adriana Dibo da CRUZ; Solange Maria de ALMEIDA (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Three-dimensional imaging modalities have been reported to be more accurate than panoramic radiographs (PR) for the assessment of bone components of the temporomandibular joint (TMJ). No exact prior information is available that demonstrates which specific limitations occur in terms of TMJ diagnosis when using PR for this purpose. This study aimed to assess the clinical validity of digital panoramic radiography (DPR) when diagnosing morphological disorders of the TMJ using cone-beam computed tomography (CBCT) images as the gold standard. A sample composed of TMJ images (N = 848), including 212 DPR and 212 CBCT images obtained from the same patient, was used to assess any morphological changes in the TMJ. Four appraisers diagnosed all of the DPR images, whereas the CBCT images were used to establish the gold standard. The reliability of each appraiser's response pattern was analyzed using the Kappa test (κ), and diagnostic tests were performed to assess each appraiser's performance using a significance level setting of 5% (α = 0.05). Reliability of each appraiser's response pattern compared to the gold standard ranged from a slight-to-moderate agreement (0.18 ≤ κ ≤ 0.45); and among the different appraisers, the response pattern showed a fair agreement (0.22 ≤ κ ≤ 0.39). Diagnostic tests showed a wide range among the different possible morphological changes diagnosed. DPR does not have validity when diagnosing morphological changes in the TMJ; it underestimates the radiological findings with higher prevalence, and thus, it cannot be used effectively as a diagnostic tool for bone components within this region.